Fentanyl transdermal system. Pain management at home. - Woodroffe, M. A. (College of Family Physicians of Canada, 1997)
PROBLEM BEING ADDRESSED: About 65% of patients with advanced malignancies experience cancer pain. Although oral opioids provide effective analgesia for most of these patients, alternate routes of drug delivery are often necessary as the disease progresses. PURPOSE OF PROGRAM: To study use of Duragesic (fentanyl transdermal system), the only transdermal opioid approved in Canada for treating chronic cancer pain in adults. MAIN COMPONENTS: Transdermal fentanyl was prescribed for a heterogeneous group of 44 patients (aged 29 to 82 years) to treat cancer pain (37 patients), chronic non-malignant pain (six patients), and pain associated with terminal AIDS (one patient), for periods of 2 to 384 days. Patients were treated individually and switched to transdermal fentanyl from other opioids when oral delivery was no longer possible. Doses were titrated as necessary and ranged from 25 micrograms/h to 300 micrograms/h. Incidental pain was treated effectively with short-acting opioids. CONCLUSIONS: Eighty percent of patients experienced good analgesia, which led to an overall improvement in their quality of life. Transdermal fentanyl was discontinued for 17% of patients due to intractable nausea, diarrhea, adherence problems, or poor analgesia. Many patients wore the system until they died or until a few days before death when severe increasing pain necessitated parenteral opioids. The side effects of transdermal fentanyl were similar to those of conventional opioids. Patient compliance and acceptance of this noninvasive, continuous system of drug delivery has been excellent; its simplicity of administration allows patients to be cared for at home.